Experiences of security and continuity of care: Patients' and families' narratives about the work of specialized palliative home care teams. Issue 2 (22nd July 2016) - Klarare, Anna; Rasmussen, Birgit H; Fossum, Bjöörn; Fürst, Carl Johan; Hansson, Johan; Hagelin, Carina Lundh
Abstract: Background: Those who are seriously ill and facing death are often living with physical, emotional, social, and spiritual suffering. Teamwork is considered to be necessary to holistically meet the diverse needs of patients in palliative care. Reviews of studies regarding palliative care team outcomes have concluded that teams provide benefits, especially regarding pain and symptom management. Much of the research concerning palliative care teams has been performed from the perspective of the service providers and has less often focused on patients' and families' experiences of care. Objective: Our aim was to investigate how the team's work is manifested in care episodes narrated by patients and families in specialized palliative home care (SPHC). Method: A total of 13 interviews were conducted with patients and families receiving specialized home care. Six patients and seven family members were recruited through SPHC team leaders. Interviews were transcribed verbatim and the transcripts qualitatively analyzed into themes. Results: Two themes were constructed through thematic analysis: (1) security ("They are always available, " "I get the help I need quickly"); and (2) continuity of care ("They know me/us, our whole situation and they really care"). Of the 74 care episodes, 50 were descriptions of regularly scheduled visits, while 24 related to acute care visits and/or interventions. Significance of results: Patients' and family members' descriptions of the work of SPHC teams are conceptualized through experiences of security and continuity of care. Experiences of security are fostered through the 24/7 availability of the team, sensitivity and flexibility in meeting patients' and families' needs, and practical adjustments to enable care at home. Experiences of continuity of care are fostered through the team's collective approach, where the individual team member knows the patients and family members, including their whole situation, and cares about the little things in life as well as caring for the family unit.